Genetic variability among U.S.-sentinel cotton plot cotton leafroll dwarf virus and globally available reference isolates based on ORF0 diversity - Adegbola, Raphael Olayemi; Ponvert, Nathaniel Donaldson; Brown, Judith K (Plant disease, 2024)
The aphid-transmitted polerovirus, cotton leafroll dwarf virus (CLRDV), first characterized from symptomatic cotton plants in South America (S.A.), has recently been identified in commercial cotton plantings in the United States (U.S.). Here, the CLRDV intra-specific diversity was investigated by comparative sequence analysis of the most divergent CLRDV coding region, ORF0/P0. Bayesian analysis of ORF0 sequences for U.S. and reference populations resolved three well-supported sister clades comprising one U.S. and two South America lineages. Principal component analysis (PCA) identified seven statistically-supported intra-specific populations. The Bayesian phylogeny- and principal component analysis (PCA) dendrogram-inferred relationships were congruent. Population analysis of ORF0 sequences indicated most lineages have evolved under negative selection, albeit certain sites/isolates evolved under positive selection. Both U.S. and South American isolates exhibited extensive ORF0 diversity. At least two U.S. invasion foci were associated with their founder populations in Alabama-Georgia (AL-GA) and eastern Texas (TX). The AL-GA founder is implicated as the source of recent widespread expansion and establishment of secondary disease foci throughout the southeastern-central U.S. Based on the geographically-restricted distribution, spread of another extant TX population appeared impeded by a population bottleneck. Extant CLRDV isolates represent several putative introductions potentially associated with catastrophic weather events dispersing viruliferous cotton aphids of unknown origin(s).